Regional Effects of Enzymatic Digestion on Knee Meniscus Cell Yield and Phenotype for Tissue Engineering - Sanchez-Adams, Johannah (Mary Ann Liebert, Inc., 2012)
An abundant cell source is the cornerstone of most tissue engineering strategies, but extracting cells from the knee meniscus is hindered by its dense fibrocartilaginous matrix. Identifying a method to efficiently isolate meniscus cells is important, as it can reduce the cost and effort required to perform meniscus engineering research. In this study, six enzymatic digestion regimens used for cartilaginous cell isolation were used to isolate cells from the outer, middle, and inner regions of the bovine knee meniscus. Each regimen in each region was assessed in terms of cell yield, impact on cell phenotype, and cytotoxicity. All digestion regimens caused an overall upregulation of cartilage-specific genes Sox9, collagen type I (Col 1), collagen type II (Col 2), cartilage oligomeric matrix protein, and aggrecan (AGC) in cells from all meniscus regions, but was highest for cells isolated using 1075 U/mL of collagenase for 3 h (high collagenase). In response to isolation, outer meniscus cells showed highest upregulation of Sox9 and Col 1 genes, whereas greatest upregulation for middle meniscus cells was seen in Col 1 expression, and Col 2 expression for inner cells. Cell yield was highest in all regions when subjected to 45 min of 61 U/mL pronase followed by 3 h of 1075 U/mL collagenase (pronase/collagenase [P/C]) digestion regimen (outer: 6.57±0.37, middle: 12.77±1.41, inner: 22.17±1.47×10(6) cells/g tissue). The second highest cell yield was achieved using the low collagenase (LC) digestion regimen that applied 433 U/mL of collagenase for 18 h (outer: 1.95±0.54, middle: 3.3±4.4, inner: 6.06±2.44×10(6) cells/g tissue). Cytotoxicity analysis showed higher cell death in the LC group compared with the P/C group. Self-assembled constructs formed from LC-isolated cells were less dense than constructs formed from P/C-isolated cells, and P/C constructs showed higher glycosaminoglycan content and compressive moduli than LC constructs. All isolation methods tested resulted in similar phenotypic changes in meniscus cells from each region. These results indicate that, compared with other common isolation protocols, the P/C isolation method is able to more efficiently isolate meniscus cells from all regions that can produce tissue engineered constructs.